Mn-CdS / In2S3-x composite material as well as preparation method and application thereof

By loading Mn-CdS nanoparticles on the surface of In2S3 microspheres, forming heterojunctions and introducing S vacancy, the photocatalytic performance of Mn-CdS/In2S3-x composite materials is improved, and the solar energy of semiconductor photocatalytic nanomaterials in the prior art is solved. The problem of low utilization rate and fast photogenerated carrier recombination achieves efficient photocatalytic degradation of organic pollutants.

CN119186597APending Publication Date: 2024-12-27NANJING NORMAL UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324141.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing semiconductor photocatalytic nanomaterials have low solar energy utilization rate, and a single In2S3 material has the problem of rapid photogenerated carrier recombination, which inhibits the performance of photocatalytic degradation of organic pollutants.

Method used

Using Mn-CdS/In2S3-x composite material, a heterojunction is formed by loading Mn-CdS nanoparticles on the surface of In2S3 microspheres, a heterojunction is formed, and a Mn-S bond is used to connect to the CdS nanoparticles, and an S vacancy is introduced to improve photocatalytic performance.

Benefits of technology

Effectively inhibit the recombination of photogenerated electron-hole pairs, accelerate the separation and migration of carriers, broaden the visible light absorption range, and improve the rate and performance of photocatalytic degradation of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186597A_ABST
    Figure CN119186597A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis, and particularly relates to a Mn-CdS / In2S3-x composite material, a preparation method and application thereof, and a method for photocatalytic degradation of organic pollutants. The composite material provided by the invention comprises In2S3-x microspheres and Mn-CdS nanoparticles loaded on the surfaces of the microspheres, and x is 1-2; the Mn-CdS nano particles comprise CdS nano particles and Mn, and the Mn is doped in the CdS nano particles; mn is connected with the CdS nano particles through Mn-S bonds. In the invention, the Mn-CdS nanoparticles and the microspheres form heterojunctions through surface-interface interaction, so that the compounding of photo-generated electron-hole pairs can be effectively inhibited, and the separation and migration of photo-generated carriers are accelerated. The loaded nano-particles are Mn-doped CdS nano-particles, and meanwhile, the In2S3 microspheres have S vacancies, so that the rate of photocatalytic degradation of organic pollutants is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalysis technology and specifically relates to a Mn-CdS / In2S 3-x Composite material, preparation method and application thereof, and method for photocatalytic degradation of organic pollutants. Background Art

[0002] With the development of industry and the extensive use of fossil fuels, environmental problems are becoming more and more serious. Semiconductor photocatalytic degradation of pollutants can use solar energy to degrade organic pollutants into small molecules, which is an effective strategy to alleviate environmental pollution. However, the solar energy utilization rate of semiconductor photocatalytic nanomaterials is still very low. At present, the development and utilization of new semiconductor photocatalytic nanomaterials is a hot topic in the field of photocatalytic technology.

[0003] Among the numerous semiconductor photocatalytic materials, sulfide photocatalysts have suitable band gap width and band edge position and are considered to be a suitable degradation photocatalyst. Among them, In2S3 has attracted people's attention due to its narrow band gap width (1.5-2.2eV) and strong light absorption performance. However, similar to other binary metal sulfides, single In2S3 materials still have the disadvantage of fast recombination of photogenerated carriers, which inhibits the performance of photocatalytic degradation of organic pollutants. Summary of the invention

[0004] The object of the present invention is to provide a Mn-CdS / In2S 3-x Composite material and preparation method and application thereof, method for photocatalytic degradation of organic pollutants, Mn-CdS / In2S 3-x As a photocatalyst, the composite material has good photocatalytic degradation performance of organic pollutants.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a Mn-CdS / In2S 3-x Composite materials, including In2S 3-x Microspheres and loaded on the In2S 3-x The Mn-CdS nanoparticles on the surface of microspheres, wherein x is 1-2; the Mn-CdS nanoparticles include CdS nanoparticles and Mn doped in the CdS nanoparticles; the Mn is connected to the CdS nanoparticles through Mn-S bonds.

[0007] Preferably, the Mn-CdS / In2S 3-x Mn-CdS and In2S in composite materials 3-x The molar ratio of is 0.05-0.2:1; the mass percentage of Mn in the Mn-CdS nanoparticles is 20-50%.

[0008] Preferably, the In2S 3-x The average particle size of the microspheres is 5 to 7 μm; the average particle size of the Mn-CdS nanoparticles is 50 to 100 nm.

[0009] The present invention also provides the Mn-CdS / In2S 3-x The method for preparing the composite material comprises the following steps:

[0010] Co-calcining CdS and a solid manganese source to obtain Mn-CdS nanoparticles;

[0011] The Mn-CdS nanoparticles, water, ethanol, a water-soluble indium source and a first water-soluble sulfur source are mixed and subjected to double decomposition reaction under alkaline conditions to obtain Mn-CdS / In2S 3-x Composite materials.

[0012] Preferably, the method for preparing CdS comprises the following steps:

[0013] The water-soluble cadmium source, the second water-soluble sulfur source and water are mixed, and a hydrothermal reaction is carried out under alkaline conditions, and solid-liquid separation is performed to obtain CdS.

[0014] Preferably, the water-soluble cadmium source is a water-soluble inorganic cadmium salt; the second water-soluble sulfur source is an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the molar ratio of the water-soluble cadmium source to the second water-soluble sulfur source is 1:2-6; the concentration of the water-soluble cadmium source in water is 0.01-0.15 mol / L;

[0015] The temperature of the hydrothermal reaction is 160-200° C., the pH value of the system is 11-13, and the reaction time is 8-16 hours.

[0016] Preferably, the solid manganese source comprises a solid inorganic manganese salt; the mass ratio of the solid manganese source to CdS is 1-5:2-8;

[0017] The co-calcination temperature is 200-400° C., and the heat preservation time is 60-240 minutes; the co-calcination is carried out in a protective gas.

[0018] Preferably, the water-soluble indium source is a water-soluble inorganic indium salt; the first water-soluble sulfur source is an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the molar ratio of In in the water-soluble indium source to the first water-soluble sulfur source is 1:2-4; the molar ratio of CdS in the Mn-CdS nanoparticles to In in the water-soluble indium source is 0.1-0.5:1;

[0019] The temperature of the double decomposition reaction is 120° C. to 200° C., the pH value of the system is 11 to 13, and the time is 6 to 24 hours.

[0020] The present invention also provides the Mn-CdS / In2S 3-x Composite material or Mn-CdS / In2S prepared by the preparation method described in the above technical solution 3-x Application of composite materials in photocatalytic degradation of organic pollutants.

[0021] The present invention also provides a method for photocatalytic degradation of organic pollutants, comprising the following steps:

[0022] The organic pollutant system is mixed with a photocatalyst and water to obtain a photocatalyst dispersion; the photocatalyst is the Mn-CdS / In2S 3-x Composite material or Mn-CdS / In2S prepared by the preparation method described in the above technical solution 3-x Composite materials;

[0023] A light source is irradiated onto the photocatalyst dispersion liquid to carry out a photocatalytic reaction.

[0024] The present invention provides a Mn-CdS / In2S 3-x Composite materials, including In2S 3-x Microspheres and loaded on the In2S 3-x Mn-CdS nanoparticles on the surface of microspheres, wherein x is 1 to 2; the Mn-CdS nanoparticles include CdS nanoparticles and Mn doped in the CdS nanoparticles; the Mn is connected to the CdS nanoparticles through Mn-S bonds. In the present invention, the Mn-CdS nanoparticles are loaded on In2S 3-x The surface forms a heterojunction through the surface-interface interaction, which can effectively inhibit the recombination of photogenerated electron-hole pairs and accelerate the separation and migration of photogenerated carriers. Compared with a single semiconductor, the nanoparticles loaded in the present invention are Mn-doped CdS nanoparticles, and S vacancies are introduced into the In2S3 microspheres, which improves the rate of photocatalytic degradation of organic pollutants. The composite photocatalyst provided by the present invention can absorb visible light below 650nm, effectively broadens the visible light absorption range of Mn-CdS, and can achieve good photocatalytic degradation of organic pollutants as a photocatalyst.

[0025] The present invention also provides the Mn-CdS / In2S 3-x The preparation method of the composite material of the invention has easy-to-obtain raw materials, a simple preparation process, few operation steps, excellent degradation performance, and provides a new idea for the rational design of semiconductor photocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 This is a scanning electron microscope image of the Mn-CdS nanoparticles prepared in Example 1;

[0028] Figure 2 Mn-CdS / In2S prepared in Example 1 3-x SEM images of the composite material;

[0029] Figure 3 is the X-ray diffraction spectrum of the Mn-CdS nanoparticles prepared in Example 2;

[0030] Figure 4 Mn-CdS / In2S prepared in Example 2 3-x X-ray diffraction spectrum of the composite material;

[0031] Figure 5 In2S prepared in Comparative Example 1 3-x EPR test image of microspheres;

[0032] Figure 6 Mn-CdS / In2S prepared in Example 1 3-x UV absorption graph of composite materials

[0033] Figure 7 Mn-CdS / In2S prepared in Example 3 3-x Degradation activity diagram of composite materials;

[0034] Figure 8 CdS / In2S prepared in Comparative Example 1 3-x Degradation activity diagram of the composites. DETAILED DESCRIPTION

[0035] The present invention provides a Mn-CdS / In2S 3-x Composite materials, including In2S 3-x Microspheres and loaded on the In2S 3-x The Mn-CdS nanoparticles on the surface of microspheres, wherein x is 1-2; the Mn-CdS nanoparticles include CdS nanoparticles and Mn doped in the CdS nanoparticles; the Mn is connected to the CdS nanoparticles through Mn-S bonds.

[0036] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0037] In the present invention, x is 1 to 2, preferably 1.2 to 1.8. S vacancies can improve the photocatalytic performance of materials in the following aspects: 1. Increasing carrier concentration: S vacancies can act as acceptor centers to capture electrons, thereby increasing the hole concentration in the material. This helps to improve the separation efficiency of photogenerated electrons and holes and reduce their recombination, thereby improving the photocatalytic efficiency. 2. Expanding the light absorption range: The introduction of S vacancies may cause lattice distortion or changes in the local band structure, which can lead to a red shift in the absorption spectrum of the material, that is, extending to a longer wavelength range and increasing the absorption of visible light. 3. Improving surface activity: The presence of S vacancies may increase the surface activity of the material and provide more active sites for photocatalytic reactions. 4. Promoting charge transfer: S vacancies can act as transmission channels for electrons and holes, promoting the transfer of charges from the bulk material to the surface, thereby increasing the rate of the photocatalytic reaction. 5. Improving the stability of the material: In some cases, S vacancies can reduce the photocorrosion of the material during the photocatalytic process and improve the long-term stability of the material. 6. Adjust the band structure: The introduction of S vacancies may change the band structure of In2S3, making it closer to the band position required by ideal photocatalytic materials to achieve reactions such as water decomposition or degradation of organic pollutants. 7. Enhance the mobility of photogenerated carriers: S vacancies may increase the mobility of carriers by reducing lattice scattering, thereby improving photocatalytic efficiency. 8. Form local microenvironments: S vacancies may form local microenvironments on the surface of the material, which may be conducive to the conduct of specific reactions.

[0038] In the present invention, the Mn-CdS / In2S 3-x Mn-CdS and In2S in composite materials 3-x The molar ratio of is preferably 0.05-0.2:1, more preferably 0.4-0.45:1; the Mn-CdS is a CdS molecule connected by Mn; the mass percentage of Mn in the Mn-CdS nanoparticles is preferably 20-50%, more preferably 30-40%. In the present invention, the Mn element is connected to the CdS nanoparticles through the Mn-S bond.

[0039] In the present invention, the In2S 3-x The average particle size of the microspheres is preferably 5-7 μm, more preferably 5-6 μm; in the embodiment of the present invention, it is specifically 5.5 μm; the average particle size of the Mn-CdS nanoparticles is preferably 50-100 nm, more preferably 60-80 nm; in the embodiment of the present invention, it is specifically 60 nm.

[0040] In the present invention, Mn-CdS nanoparticles are loaded on In2S 3-xThe surface forms a heterojunction through the surface-interface interaction, which can effectively inhibit the recombination of photogenerated electron-hole pairs and accelerate the separation and migration of photogenerated carriers. Compared with a single semiconductor, the nanoparticles loaded in the present invention are Mn-doped CdS nanoparticles, and S vacancies are introduced into the In2S3 microspheres, which improves the rate of photocatalytic degradation of organic pollutants. The composite photocatalyst provided by the present invention can absorb visible light below 650nm, effectively broadens the visible light absorption range of Mn-CdS, and can achieve good photocatalytic degradation of organic pollutants as a photocatalyst.

[0041] The present invention also provides the Mn-CdS / In2S 3-x The method for preparing the composite material comprises the following steps:

[0042] Co-calcining CdS and a solid manganese source to obtain Mn-CdS nanoparticles;

[0043] The Mn-CdS nanoparticles, water, ethanol, a water-soluble indium source and a first water-soluble sulfur source are mixed and subjected to double decomposition reaction under alkaline conditions to obtain Mn-CdS / In2S 3-x Composite materials.

[0044] The invention co-calcines CdS and a solid manganese source to obtain Mn-CdS nanoparticles.

[0045] In the present invention, the method for preparing CdS preferably comprises the following steps:

[0046] The water-soluble cadmium source, the second water-soluble sulfur source and water are mixed, and a hydrothermal reaction is carried out under alkaline conditions, and solid-liquid separation is performed to obtain CdS.

[0047] In the present invention, the water-soluble cadmium source is preferably a water-soluble inorganic cadmium salt; the water-soluble inorganic cadmium salt preferably includes one or more of cadmium nitrate, cadmium acetate, cadmium chloride and cadmium sulfate, more preferably cadmium nitrate and / or cadmium acetate; the cadmium acetate is preferably cadmium acetate dihydrate; the second water-soluble sulfur source is preferably an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the inorganic water-soluble sulfur source preferably includes sodium sulfide and / or potassium sulfide, more preferably sodium sulfide; the organic water-soluble sulfur source preferably includes thioacetamide and / or dithioacetamide, more preferably thioacetamide; the molar ratio of the water-soluble cadmium source to the second water-soluble sulfur source is preferably 1:2-6, more preferably 1:3-5, most preferably 1:3; the concentration of the water-soluble cadmium source in water is preferably 0.01-0.15 mol / L, more preferably 0.06-0.14 mol / L, most preferably 0.08-0.12 mol / L.

[0048] The present invention has no special requirements for the mixing method, and a dispersion method well known to those skilled in the art can be used, such as stirring or ultrasound; when the mixing is stirring, the stirring speed is preferably 200 to 600 rpm.

[0049] In the present invention, the temperature of the hydrothermal reaction is preferably 160-200°C, more preferably 170-190°C, and most preferably 180°C; the system pH value is preferably 11-13, more preferably 12-13, and most preferably 13; the time is preferably 8-16h, more preferably 10-15h, and most preferably 12h; the reagent providing the alkaline environment is preferably sodium hydroxide; the molar ratio of the water-soluble cadmium source and sodium hydroxide is preferably 1:2-6, more preferably 1:2-4; the role of the sodium hydroxide is to adjust the pH value, and will not introduce other impurities to cause precipitation to affect the reaction.

[0050] The present invention has no special requirements for the solid-liquid separation method, and can adopt solid-liquid separation methods well known in the art, such as centrifugation; after the solid-liquid separation, the present invention preferably further includes washing and drying the obtained solid with anhydrous methanol to obtain the CdS; the particle size of the CdS is preferably 50 to 100 nm, more preferably 60 to 90 nm.

[0051] In the present invention, the solid manganese source is preferably a solid inorganic manganese salt; the solid inorganic manganese salt preferably includes manganese chloride and / or manganese acetate; the manganese acetate is preferably manganese acetate dihydrate; the mass ratio of the solid manganese source to CdS is preferably 1-5:2-8, more preferably 1-3:5-8.

[0052] In the present invention, the co-calcination preferably includes: placing the solid manganese source and CdS at the upstream and downstream of the furnace body for co-calcination; the furnace body is preferably a tubular furnace; the co-calcination temperature is preferably 200-400°C, more preferably 250-350°C, and most preferably 300°C; the holding time is preferably 60-240min, more preferably 90-210min, and most preferably 120-180min; the co-calcination is preferably carried out in a protective gas, and more preferably in a nitrogen atmosphere; the present invention has no special requirements for the heating rate of heating to the co-calcination temperature, and the heating rate well known in the art can be used; the co-calcination also preferably includes cooling; the cooling is preferably natural cooling. In an embodiment of the present invention, the heating rate is 5°C / min. In the co-calcination process of the present invention, the introduction of the solid manganese source can form a Cd-S-Mn bond, so that CdS is converted into Mn-CdS nanoparticles.

[0053] In the present invention, the particle size of the Mn-CdS nanoparticles is preferably 50 to 100 nm, more preferably 60 to 100 nm.

[0054] After obtaining the Mn-CdS nanoparticles, the present invention mixes the Mn-CdS nanoparticles, water, ethanol, a water-soluble indium source and a first water-soluble sulfur source, and performs a double decomposition reaction under alkaline conditions to obtain Mn-CdS / In2S 3-x Composite materials.

[0055] In the present invention, the water-soluble indium source is preferably a water-soluble inorganic indium salt; the water-soluble inorganic indium salt is preferably indium chloride and / or indium nitrate; the first water-soluble sulfur source is preferably an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the inorganic water-soluble sulfur source preferably includes sodium sulfide and / or potassium sulfide, more preferably sodium sulfide; the organic water-soluble sulfur source preferably includes thioacetamide and / or dithioacetamide, more preferably thioacetamide; the indium chloride is preferably indium trichloride and / or indium trichloride tetrahydrate; the molar ratio of In in the water-soluble indium source to the first water-soluble sulfur source is preferably 1:2-4, more preferably 1:2-3; the molar ratio of CdS in the Mn-CdS nanoparticles to In in the water-soluble indium source is preferably 0.1-0.5:1, more preferably 0.4-0.45:1.

[0056] In the present invention, the volume ratio of water to ethanol is preferably 1:1-2, more preferably 1:1; the water is preferably deionized water; the concentration of the water-soluble indium source in the double decomposition reaction system is preferably 0.02-0.14 mol / L, more preferably 0.08-0.13 mol / L.

[0057] In the present invention, the mixing order is preferably: first dissolving the Mn-CdS nanoparticles in water and ethanol, and then sequentially adding the water-soluble indium source and the first water-soluble sulfur source.

[0058] In the present invention, the hydrothermal reaction is preferably carried out in a reactor with a polytetrafluoroethylene lining; the polytetrafluoroethylene lining of the reactor is preferably pretreated before the hydrothermal reaction; the pretreatment is preferably cleaning and drying; the cleaning preferably includes aqua regia cleaning and deionized water cleaning in sequence; the present invention has no special requirements for the cleaning method, and the cleaning method familiar to those skilled in the art can be used; the drying is preferably vacuum drying at 60°C for 8 hours.

[0059] In the present invention, the temperature of the double decomposition reaction is preferably 120-200°C, more preferably 160-190°C, and most preferably 180°C; the system pH value is preferably 11-13, more preferably 12-13, and most preferably 13; the time is preferably 6-24h, more preferably 8-16h, and further preferably 12h; the double decomposition reaction is preferably carried out under oil bath conditions; the reagent providing the alkaline environment is preferably urea or sodium hydroxide, more preferably urea; the molar ratio of In to urea in the water-soluble indium source is preferably 1:1-2, more preferably 1:1-1.5; in the process of the double decomposition reaction of the present invention, the Mn-CdS nanoparticles are deposited on In2S 3-x The surface of In2S loaded with Mn-CdS was obtained. 3-x Microspheres. The present invention generates thermal defects by high temperature and prolonged reaction time to form S vacancies. Specifically, during the crystal growth process, due to thermal vibration, atoms may obtain enough energy to escape from their equilibrium positions, thereby leaving vacancies at the original positions. The formation of vacancies is affected by temperature, and the vacancy concentration increases at high temperatures. Vacancies can migrate to the crystal surface or internal gaps to form different types of vacancies.

[0060] In the present invention, after the double decomposition reaction, the obtained product system is preferably subjected to solid-liquid separation, and the obtained solid is washed and dried to obtain Mn-CdS / In2S 3-x Composite material; the present invention has no special requirements for the washing method, and a washing method familiar to those skilled in the art can be used, such as washing with a mixture of water and ethanol; the present invention has no special requirements for the drying method, and a drying method familiar to those skilled in the art can be used, such as drying naturally in the air.

[0061] The preparation method of the invention has readily available raw materials, a simple preparation process, fewer operation steps, and excellent degradation performance, and provides a new idea for the rational design of semiconductor photocatalysts.

[0062] The present invention also provides the Mn-CdS / In2S 3-x Composite material or Mn-CdS / In2S prepared by the preparation method described in the above technical solution 3-x Application of composite materials in photocatalytic degradation of organic pollutants.

[0063] In the present invention, the Mn-CdS / In2S 3-x The application of the composite material in the photocatalytic degradation of organic pollutants is preferably as a photocatalyst; the organic pollutants are preferably antibiotics, more preferably tetracycline antibiotics, and most preferably tetracycline; the present invention does not have any special limitation on the process of the application, and a method familiar to those skilled in the art can be used.

[0064] The present invention also provides a method for photocatalytic degradation of organic pollutants, comprising the following steps:

[0065] The organic pollutant system is mixed with a photocatalyst and water to obtain a photocatalyst dispersion; the photocatalyst is the Mn-CdS / In2S 3-x Composite material or Mn-CdS / In2S prepared by the preparation method described in the above technical solution 3-x Composite materials;

[0066] A light source is irradiated onto the photocatalyst dispersion liquid to carry out a photocatalytic reaction.

[0067] The present invention mixes the system containing organic pollutants with a photocatalyst and water to obtain a photocatalyst dispersion.

[0068] In the present invention, the mixing is preferably carried out under dark conditions; the mixing method is preferably stirring, and the time is preferably 0.5 to 2 hours, more preferably 1 to 2 hours; the present invention does not have any special limitation on the stirring speed, as long as the photocatalyst dispersion can be evenly dispersed and reach adsorption-desorption equilibrium.

[0069] In the present invention, the system containing organic pollutants is preferably an antibiotic system, more preferably a tetracycline antibiotic system, and most preferably a tetracycline system; the concentration of organic pollutants in the photocatalyst dispersion is preferably 30 to 60 mg / L, more preferably 40 to 50 mg / L; the concentration of the photocatalyst is preferably 0.5 to 3 g / L, more preferably 1 to 2 g / L.

[0070] The photocatalyst dispersion liquid is obtained, and the present invention irradiates the photocatalyst dispersion liquid with a light source to perform degradation.

[0071] In the present invention, the light source is preferably Xe light or visible light; the temperature of the photocatalytic reaction is preferably 20-30°C, more preferably 25-30°C; the time is preferably 100-150 min, more preferably 120-140 min; the temperature is preferably maintained by circulating water cooling.

[0072] To further illustrate the present invention, the following is a schematic diagram of the Mn-CdS / In2S 3-x The composite material, its preparation method and application, and the method for photocatalytic degradation of organic pollutants are described in detail, but they should not be understood as limiting the protection scope of the present invention.

[0073] Example 1

[0074] (1) Preparation of CdS nanoparticles: 2.665 g of cadmium acetate dihydrate (Cd(CH3COO)2·2H2O) and 2.341 g of sodium sulfide (Na2S) were weighed and dispersed in 80 ml of deionized water, and an appropriate amount of sodium hydroxide (NaOH) was added to adjust the pH to 13. After continuous stirring for 30 min, the mixed solution in the step was transferred to a polytetrafluoroethylene-lined reactor, heated at 160° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in the step was subsequently washed and centrifuged, and after separation, vacuum dried at 60° C. overnight to obtain CdS;

[0075] (2) Preparation of Mn-CdS nanoparticles: 0.8 g of manganese chloride tetrahydrate (MnCl2·4H2O) and 0.576 g of CdS prepared in step (1) were weighed and placed in porcelain boats A and B, respectively. The quartz boats A and B in the step were placed in the upstream and downstream of a tube furnace, and calcined at high temperature in a nitrogen inert atmosphere at a heating rate of 5°C / min from room temperature to 400°C, and kept warm for 60 min. After natural cooling, the sample in porcelain boat B was collected to obtain Mn-CdS nanoparticles;

[0076] (4) Preparation of Mn-CdS / In2S 3-x Composite photocatalyst: 0.0326 g of Mn-CdS prepared in step (2) was weighed and dispersed in a mixed solution of 25 mL of deionized water and 25 mL of ethanol, and 0.2933 g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501 g of thioacetamide (TAA), and 0.1 g of urea were added in sequence. The mixed solution in this step was transferred to a round-bottom flask, heated with stirring at 180° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in this step was then washed and centrifuged. After separation, it was vacuum dried at 60° C. overnight to obtain Mn-CdS / In2S 3-x A composite material, wherein the loading amount of Mn-CdS nanoparticles in the composite material is 20wt%, and x is 1.5.

[0077] The Mn-CdS nanoparticles and Mn-CdS / In2S 3-x The composite material was tested using a scanning electron microscope, and the resulting SEM image is shown in the figure below. Figure 1 and Figure 2 shown.

[0078] Depend on Figure 1 and Figure 2 It can be seen that Mn-CdS / In2S 3-x The morphology of the composite material is mainly composed of Mn-CdS particles uniformly loaded on the surface of In2S3. At the same time, it can be seen that the CdS after manganese doping has a larger specific surface area, which is comparable to In2S 3-xThe heterojunction is formed by the surface-interface interaction, which expands the visible light absorption region. Figure 2 It can also be seen that In2S 3-x The average particle size of the microspheres is 5.5 μm, and the average particle size of the Mn-CdS nanoparticles is 60 nm.

[0079] Example 2

[0080] (1) Preparation of CdS nanoparticles: 2.665 g of cadmium acetate dihydrate (Cd(CH3COO)2·2H2O) and 2.341 g of sodium sulfide (Na2S) were weighed and dispersed in 80 ml of deionized water, and an appropriate amount of sodium hydroxide (NaOH) was added to adjust the pH to 13. After continuous stirring for 30 min, the mixed solution in the step was transferred to a polytetrafluoroethylene-lined reactor, heated at 160° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in the step was subsequently washed and centrifuged, and after separation, vacuum dried at 60° C. overnight to obtain CdS;

[0081] (2) Preparation of Mn-CdS nanoparticles: 0.8 g of manganese chloride tetrahydrate (MnCl2·4H2O) and 0.576 g of CdS prepared in step (1) were weighed and placed in porcelain boats A and B, respectively. The quartz boats A and B in the step were placed in the upstream and downstream of a tube furnace, and calcined at high temperature in a nitrogen inert atmosphere at a heating rate of 5°C / min from room temperature to 400°C, and kept warm for 60 min. After natural cooling, the sample in porcelain boat B was collected to obtain Mn-CdS nanoparticles;

[0082] (3) Preparation of Mn-CdS / In2S 3-x Composite photocatalyst: 0.0488 g of Mn-CdS prepared in step (2) was weighed and dissolved in a mixed solution of 25 mL of deionized water and 25 mL of ethanol, and 0.2933 g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501 g of thioacetamide (TAA), and 0.1 g of urea were added in sequence. The mixed solution in this step was transferred to a round-bottom flask, heated with stirring at 180° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in this step was then washed and centrifuged. After separation, it was vacuum dried at 60° C. overnight to obtain Mn-CdS / In2S 3-x A composite material, wherein the loading amount of Mn-CdS nanoparticles in the composite material is 30wt%, and x is 1.5.

[0083] The Mn-CdS nanoparticles, Mn-CdS / In2S 3-x The composite materials were subjected to XRD tests, and the obtained XRD diffraction patterns were as follows: Figure 3 , Figure 4 shown.

[0084] Depend on Figure 3 It can be seen that the three strongest peaks of XRD correspond to (100), (002), and (101), indicating that the present invention successfully obtains Mn-CdS material through manganese doping treatment.

[0085] Depend on Figure 4 It can be seen that the XRD peaks appear at 27.4°, 47.7°, and 33.2°, corresponding to (311), (440), and (400) (PDF#84-1385), indicating that the present invention successfully obtained Mn-CdS / In2S by manganese doping treatment. 3-x Composite materials.

[0086] Example 3

[0087] (1) Preparation of CdS nanoparticles: 2.665 g of cadmium acetate dihydrate (Cd(CH3COO)2·2H2O) and 2.341 g of sodium sulfide (Na2S) were weighed and dispersed in 80 ml of deionized water, and an appropriate amount of sodium hydroxide (NaOH) was added to adjust the pH to 13. After continuous stirring for 30 min, the mixed solution in the step was transferred to a polytetrafluoroethylene-lined reactor, heated at 160° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in the step was subsequently washed and centrifuged, and after separation, vacuum dried at 60° C. overnight to obtain CdS;

[0088] (2) Preparation of Mn-CdS nanoparticles: 0.8 g of manganese chloride tetrahydrate (MnCl2·4H2O) and 0.576 g of CdS prepared in step (1) were weighed and placed in porcelain boats A and B, respectively. The quartz boats A and B in the step were placed in the upstream and downstream of a tube furnace, and calcined at high temperature in a nitrogen inert atmosphere at a heating rate of 5°C / min from room temperature to 400°C, and kept warm for 60 min. After natural cooling, the sample in porcelain boat B was collected to obtain Mn-CdS nanoparticles;

[0089] (3) Preparation of Mn-CdS / In2S 3-x Composite photocatalyst: 0.0651 g of Mn-CdS prepared in step (2) was weighed and dissolved in a mixed solution of 25 mL of deionized water and 25 mL of ethanol, and 0.2933 g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501 g of thioacetamide (TAA), and 0.1 g of urea were added in sequence. The mixed solution in this step was transferred to a round-bottom flask, heated with stirring at 180° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in this step was then washed and centrifuged. After separation, it was vacuum dried at 60° C. overnight to obtain Mn-CdS / In2S 3-x A composite material, wherein the loading amount of Mn-CdS nanoparticles in the composite material is 40wt%, and x is 1.5.

[0090] Comparative Example 1

[0091] (1) Preparation of CdS nanoparticles: 2.665 g of cadmium acetate dihydrate (Cd(CH3COO)2·2H2O) and 2.341 g of sodium sulfide (Na2S) were weighed and dispersed in 80 ml of deionized water, and an appropriate amount of sodium hydroxide (NaOH) was added to adjust the pH to 13. After continuous stirring for 30 min, the mixed solution in the step was transferred to a polytetrafluoroethylene-lined reactor, heated at 160° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in the step was subsequently washed and centrifuged. After separation, it was vacuum dried at 60° C. overnight to obtain CdS;

[0092] (2) Preparation of CdS / In2S 3-x Composite material: 0.0651 g of CdS prepared in step (1) was weighed and dissolved in a mixed solution of 25 mL of deionized water and 25 mL of ethanol, and 0.2933 g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501 g of thioacetamide (TAA), and 0.1 g of urea were added in sequence. The mixed solution in this step was transferred to a round-bottom flask, heated with stirring at 180° C. for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in this step was then washed and centrifuged. After separation, it was vacuum dried at 60° C. overnight to obtain CdS / In2S 3-x A composite material, wherein the loading amount of CdS nanoparticles in the composite material is 40wt%, and x is 1.5.

[0093] Comparative Example 2

[0094] Preparation of In2S 3-x Photocatalyst: 0.2933 g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501 g of thioacetamide (TAA), and 0.1 g of urea (H2NCONH2) were weighed and dissolved in a mixed solution of 25 mL of deionized water and 25 mL of ethanol. The mixed solution in this step was transferred to a round-bottom flask, heated with stirring at 180°C for 12 h, and naturally cooled to obtain a precipitate. The precipitate obtained in this step was then washed and centrifuged. After separation, it was vacuum dried at 60°C overnight to obtain In2S 3-x The photocatalyst, wherein x is 1.5. 3-x Perform EPR test, see the results Figure 5 .

[0095] Depend on Figure 5 It can be seen that in In2S 3-x The S vacancy signal was detected in the In2S 3-x There is an S vacancy in it.

[0096] Comparative Example 3

[0097] Preparation of In2S3 photocatalyst: Weigh 0.2933g of indium chloride tetrahydrate (InCl3·4H2O), 0.1501g of thioacetamide (TAA), and 0.1g of urea (H2NCONH2) and dissolve them in a mixed solution of 25mL of deionized water and 25mL of ethanol. The mixed solution described in this step is transferred to a round-bottom flask, heated with stirring at 60°C for 2h, and a precipitate is obtained after natural cooling. The precipitate obtained in this step is then washed and centrifuged. After separation, it is vacuum dried at 60°C overnight to obtain an In2S3 photocatalyst.

[0098] Test Example 1

[0099] The In2S of Comparative Example 2 3-x and Mn-CdS in Example 3, 40%-Mn-CdS / In2S 3-x Scanning on a solid ultraviolet absorption spectrometer, the ultraviolet absorption spectrum is shown in Figure 6 .

[0100] Depend on Figure 6 It can be seen that In2S 3-x The absorption threshold of Mn-CdS is at 650nm, the absorption threshold of Mn-CdS is at 550nm, and the absorption threshold of 40%-Mn-CdS / In2S 3-x The absorption threshold is at 600nm.

[0101] Test Example 2

[0102] The composite materials of Examples 1 to 3 and Comparative Examples 1 and 3 and the In2S 3-x As a photocatalyst, the photocatalytic degradation of tetracycline was tested under 500WXe light (90mW cm -2 ) irradiation to carry out photocatalytic degradation experiment. The photocatalytic degradation tetracycline test method comprises the following steps: dispersing 50 mg of photocatalyst in 50 mL of tetracycline hydrochloride aqueous solution (50 mg / L); placing the mixed solution in a photocatalytic reaction device, and then stirring the photocatalyst dispersion in the dark for 1 hour to reach adsorption-desorption equilibrium. The dispersion was then irradiated with Xe light and cooled with circulating water to keep the system temperature at 25°C. The dispersion was irradiated for 120 minutes, and 3 mL aliquots were extracted every 30 minutes and filtered through a membrane with 0.22 μm pores. The filtrate was then spectrophotometrically evaluated using a UV-2600 ultraviolet-visible spectrophotometer, which showed that TCH had a maximum absorbance of 357 nm. Mn-CdS / In2S prepared in Example 3 3-x The degradation activity of the composite material is shown in Figure 2. Figure 7 As shown, the CdS / In2S prepared in Comparative Example 13-x The degradation activity of the composite material is shown in Figure 2. Figure 8 shown.

[0103] Depend on Figure 7 It can be seen that Mn-CdS / In2S 3-x The composite photocatalyst has good photocatalytic degradation activity of tetracycline, among which 40%-Mn-CdS / In2S 3-x The degradation rate of the photocatalyst under full spectrum visible light can reach 74% in 2 hours. 3-x The photocatalytic degradation rate increased by 1.4 times, which is much higher than the existing In2S 3-x The catalytic performance of the composite photocatalyst is improved. 3-x The degradation performance is also improved compared to In2S3.

[0104] Depend on Figure 8 It can be seen that the prepared CdS / In2S 3-x The performance of the composite photocatalyst for tetracycline degradation is far inferior to that of Mn-CdS / In2S after manganese doping 3-x Composite photocatalyst. This is due to the formation of Cd-S-Mn bonds during the manganese doping process of the present invention, and the In2S 3-x Through the strong interaction between the surface and interface, a heterojunction is formed, which accelerates the separation and transportation of photogenerated carriers, significantly improves the degradation rate, and exhibits excellent photocatalytic performance.

[0105] The degradation rate data of the embodiments and comparative examples under Xe lamp irradiation for 2 h are shown in Table 1.

[0106] Table 1 Degradation rate of the examples and comparative examples under Xe lamp irradiation for 2 h

[0107] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Degradation rate (%) 69 70 74 42 51 41

[0108] It can be seen from Table 1 that under the same conditions, the 20wt% Mn-CdS / In2S 3-x The degradation rate is 69%, and the 30wt% Mn-CdS / In2S in Example 2 3-x The degradation rate is 70%, and the 40wt% Mn-CdS / In2S in Example 3 3-x The degradation rate is 74%, and the 40wt% CdS / In2S in Comparative Example 1 3-x The degradation rate is 42%, and the In2S 3-x The degradation rate is 51%, and the degradation rate of In2S3 in Comparative Example 3 is 41%. It can be seen that in the embodiment, the 40wt% Mn-CdS / In2S 3-xThe composite material has the best degradation performance. In the comparative example, In2S with S vacancies 3-x The degradation performance is better than that of In2S3, which proves that the introduction of vacancies and element doping in the present invention improves the catalytic performance of the photocatalyst.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A Mn-CdS / In2S 3-x A composite material, characterized in that Including In2S 3-x Microspheres and loaded on the In2S 3-x The Mn-CdS nanoparticles on the surface of microspheres, wherein x is 1-2; the Mn-CdS nanoparticles include CdS nanoparticles and Mn doped in the CdS nanoparticles; the Mn is connected to the CdS nanoparticles through Mn-S bonds.

2. Mn-CdS / In2S according to claim 1 3-x A composite material, characterized in that The Mn-CdS / In2S 3-x Mn-CdS and In2S in composite materials 3-x The molar ratio of is 0.05-0.2:1; the mass percentage of Mn in the Mn-CdS nanoparticles is 20-50%.

3. Mn-CdS / In2S according to claim 1 or 2 3-x A composite material, characterized in that The In2S 3-x The average particle size of the microspheres is 5 to 7 μm; the average particle size of the Mn-CdS nanoparticles is 50 to 100 nm.

4. The Mn-CdS / In2S according to any one of claims 1 to 3 3-x A method for preparing a composite material, characterized in that: The following steps are involved: Co-calcining CdS and a solid manganese source to obtain Mn-CdS nanoparticles; The Mn-CdS nanoparticles, water, ethanol, a water-soluble indium source and a first water-soluble sulfur source are mixed and subjected to double decomposition reaction under alkaline conditions to obtain Mn-CdS / In2S 3-x Composite materials.

5. The preparation method according to claim 4, characterized in that: The preparation method of CdS comprises the following steps: The water-soluble cadmium source, the second water-soluble sulfur source and water are mixed, and a hydrothermal reaction is carried out under alkaline conditions, and solid-liquid separation is performed to obtain CdS.

6. The preparation method according to claim 5, characterized in that: The water-soluble cadmium source is a water-soluble inorganic cadmium salt; the second water-soluble sulfur source is an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the molar ratio of the water-soluble cadmium source to the second water-soluble sulfur source is 1:2-6; the concentration of the water-soluble cadmium source in water is 0.01-0.15 mol / L; The temperature of the hydrothermal reaction is 160-200° C., the pH value of the system is 11-13, and the reaction time is 8-16 hours.

7. The preparation method according to claim 4, characterized in that: The solid manganese source includes a solid inorganic manganese salt; the mass ratio of the solid manganese source to CdS is 1-5:2-8; The co-calcination temperature is 200-400° C., and the heat preservation time is 60-240 minutes; the co-calcination is carried out in a protective gas.

8. The preparation method according to claim 4, characterized in that: The water-soluble indium source is a water-soluble inorganic indium salt; the first water-soluble sulfur source is an inorganic water-soluble sulfur source and / or an organic water-soluble sulfur source; the molar ratio of In in the water-soluble indium source to the first water-soluble sulfur source is 1:2-4; the molar ratio of CdS in the Mn-CdS nanoparticles to In in the water-soluble indium source is 0.1-0.5:1; The temperature of the double decomposition reaction is 120° C. to 200° C., the pH value of the system is 11 to 13, and the time is 6 to 24 hours.

9. The Mn-CdS / In2S according to any one of claims 1 to 3 3-x Composite material or Mn-CdS / In2S prepared by the method according to any one of claims 4 to 8 3-x Application of composite materials in photocatalytic degradation of organic pollutants.

10. A method for photocatalytic degradation of organic pollutants, characterized in that: The following steps are involved: The organic pollutant system is mixed with a photocatalyst and water to obtain a photocatalyst dispersion; the photocatalyst is the Mn-CdS / In2S 3-x Composite material or Mn-CdS / In2S prepared by the method according to any one of claims 4 to 8 3-x Composite materials; A light source is irradiated onto the photocatalyst dispersion liquid to carry out a photocatalytic reaction.